Palbociclib with adjuvant endocrine therapy in early breast cancer (PALLAS): interim analysis of a multicentre, open-label, randomised, phase 3 study. Issue 2 (February 2021) - Mayer, Erica L; Dueck, Amylou C; Martin, Miguel; Rubovszky, Gabor; Burstein, Harold J; Bellet-Ezquerra, Meritxell; Miller, Kathy D; Zdenkowski, Nicholas; Winer, Eric P; Pfeiler, Georg; Goetz, Matthew; Ruiz-Borrego, Manuel; et al.
Summary: Background: Palbociclib added to endocrine therapy improves progression-free survival in hormone-receptor-positive, HER2-negative, metastatic breast cancer. The PALLAS trial aimed to investigate whether the addition of 2 years of palbociclib to adjuvant endocrine therapy improves invasive disease-free survival over endocrine therapy alone in patients with hormone-receptor-positive, HER2-negative, early-stage breast cancer. Methods: PALLAS is an ongoing multicentre, open-label, randomised, phase 3 study that enrolled patients at 406 cancer centres in 21 countries worldwide with stage II–III histologically confirmed hormone-receptor-positive, HER2-negative breast cancer, within 12 months of initial diagnosis. Eligible patients were aged 18 years or older with an Eastern Cooperative Oncology Group performance score of 0 or 1. Patients were randomly assigned (1:1) in permuted blocks of random size (4 or 6), stratified by anatomic stage, previous chemotherapy, age, and geographical region, by use of central telephone-based and web-based interactive response technology, to receive either 2 years of palbociclib (125 mg orally once daily on days 1–21 of a 28-day cycle) with ongoing standard provider or patient-choice adjuvant endocrine therapy (tamoxifen or aromatase inhibitor, with or without concurrent luteinising hormone-releasing hormone agonist), or endocrine therapy alone, without masking. The primary endpoint of the study was invasive disease-free survival in the intention-to-treat population. Safety was assessed in all randomly assigned patients who started palbociclib or endocrine therapy. This report presents results from the second pre-planned interim analysis triggered on Jan 9, 2020, when 67% of the total number of expected invasive disease-free survival events had been observed. The trial is registered with ClinicalTrials.gov (NCT02513394 ) and EudraCT (2014-005181-30). Findings: Between Sept 1, 2015, and Nov 30, 2018, 5760 patients were randomly assigned to receive palbociclib plus endocrine therapy (n=2883) or endocrine therapy alone (n=2877). At the time of the planned second interim analysis, at a median follow-up of 23·7 months (IQR 16·9–29·2), 170 of 2883 patients assigned to palbociclib plus endocrine therapy and 181 of 2877 assigned to endocrine therapy alone had invasive disease-free survival events. 3-year invasive disease-free survival was 88·2% (95% CI 85·2–90·6) for palbociclib plus endocrine therapy and 88·5% (85·8–90·7) for endocrine therapy alone (hazard ratio 0·93 [95% CI 0·76–1·15]; log-rank p=0·51). As the test statistic comparing invasive disease-free survival between groups crossed the prespecified futility boundary, the independent data monitoring committee recommended discontinuation of palbociclib in patients still receiving palbociclib and endocrine therapy. The most common grade 3–4 adverse events were neutropenia (1742 [61·3%] of 2840 patients on palbociclib and endocrine therapy vs 11 [0·3%] of 2903 on endocrine therapy alone), leucopenia (857 [30·2%] vs three [0·1%]), and fatigue (60 [2·1%] vs ten [0·3%]). Serious adverse events occurred in 351 (12·4%) of 2840 patients on palbociclib plus endocrine therapy versus 220 (7·6%) of 2903 patients on endocrine therapy alone. There were no treatment-related deaths. Interpretation: At the planned second interim analysis, addition of 2 years of adjuvant palbociclib to adjuvant endocrine therapy did not improve invasive disease-free survival compared with adjuvant endocrine therapy alone. On the basis of these findings, this regimen cannot be recommended in the adjuvant setting. Long-term follow-up of the PALLAS population and correlative studies are ongoing. Funding: Pfizer.